PENGARUH RAPAT KEADAAN CELAH ENERGI TERHADAP KARAKTERISTIK ID-VG AMORPHOUS SILICON THIN FILM TRANSISTOR (A-SI TFT) - Mardiana Silangen, Patricia
Abstract: The effects of density of state (DOS) function on the ID-VG characteristic of amorphous silicon thin film transistor (a-Si TFT) was simulated. Transport equations of TFT were solved by using finite element method. A Specific formula was developed to calculate the drain current of TFT. The effects of tail states and mid gap states of a-Si on ID-VG characteristic of TFT were also investigated. It was found that the tail states of a-Si strongly affected the drain current of TFT. The simulation carried out in this study is able to describe the performance of a-Si TFT.